Halal Tourism in the Perspective of the Qur'an and Hadith and Maqashid Syari'ah - Firdaus Firdaus; Desmadi Saharuddin; Ilda Hayati (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Tourism has enormous benefits in Islam and even has a positive impact on One's faith. Tourism is a part of